Theorising materiality in children's digital books - Kucirkova, Natalia (Array, 2019)
Participatory literacies are new ways of experiencing narratives and of "interpreting, making, sharing and belonging in increasingly globally and digitally mediated cultures" (Wohlwend 2017a: 62). This paper discusses the material features of children’s digital books and the extent to which they support participatory literacies. The material features of digital books are conceptualised in terms of their external and internal properties. Based on a theoretical discussion and empirical observations it is argued that specific internal material properties of children’s digital books, namely their interactivity and multimedia, are uniquely positioned to support participatory literacies and are therefore a site of novelty in children’s experiences of narratives.